Turnover Intention Karyawan: Pengaruh Budaya Organisasi, Organizational Justice dan Kepuasan Kerja - Noerchoidah, Noerchoidah (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 2 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i02.p12, 2020)
The purpose of this study is to analyze the application of the concept of turnover intention to hotel employees in Surabaya-Indonesia, with a focus on the role of the construct of job satisfaction as a mediating variable. This research also aims to analyze the influence of organizational culture variables and organizational justice on job satisfaction, and to analyze the effect of job satisfaction on turnover intention. This research was conducted on 152 hotel employees in Surabaya with purposive sampling. The results of distributing questionnaires were processed using Partial Least Square (PLS) analysis techniques. There are 7 hypotheses proposed in this study, 6 hypotheses are supported, namely H1, H2, H4, H5, H6, and H7. While H3 is not supported. The results of this study support social exchange theory. The holistic conclusion of this study is that this research model is supported empirically.